Studies related to ammonia metabolism in mammalian tissues - Brosnan, JT (1968)
The work reported in this thesis concerns the metabolism of ammonia in the liver and kidney of the rat. Glutamate dehydrogenase in the mitochondria of these tissues appears to be very close to equilibrium and thus ammonia is linked to a large number of other metabolites through the network of equilibrium enzymes in these tissues, These inter-relations and the factors influencing them in a number of different situations were studied. Chapter I contains a historical introduction to the metabolism of ammonia and a discussion of the difficulties inherent in a study of its metabolism. Rapid freezing of tissues together with an enzymatic method for the determination of ammonia provide the best methods for the study of its in vivo metabolism. A very brief account of current knowledge concerning equilibrium enzymes is presented and the criteria necessary for establishing that the reaction of a given enzyme is close to equilibrium are discussed. As an arbitrary standard, it is proposed that the in in vivo mass action ratio should differ from the apparent equilibrium constant by no more than a factor of three before it may be considered to be ‘close to equilibrium’. Continued in thesis ...